Cristo Rey St. Martin College Preparatory School : promoting a culture of continuous improvement - Berger, Gail; Howard, Liz (London : Kellogg School of Management, 2019)
Cristo Rey St. Martin College Preparatory (CRSM), a school with a unique educational model, has built a culture of accountability and student achievement. Founded in 2004 with a mission of serving "young people of limited economic means," the school had a rocky start. It was plagued with student failure, high teacher turnover, and a total lack of accountability on the part of both students and teachers. In 2008, a new principal, Michael Odiotti, was hired to turn around the school. During his early years as principal, Mr. Odiotti faced many challenges, including poor academic results, lack of discipline, the threat of bankruptcy, and insufficient employers to support the school's work-study program. By 2018, the school had overcome some of these obstacles, and its metrics were exemplary. The question CRSM currently faces is how it can bolster a new culture of continuous improvement to avoid complacency while continuing to push accountability to achieve even greater results.
Originally Published InBerger, G., & Howard, L. (2019). Cristo Rey St. Martin College Preparatory School: Promoting a Culture of Continuous Improvement. 5-218-254. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Educational accountability; Academic achievement; Preparatory schools -- Illinois -- Waukegan